Cognitive and metacognitive aspects of the development of lifelong learning competencies in law students - Grokholskyi, V. L.; Kaida, N. I.; Albul, S. V.; Ryzhkov, E. V.; Trehub, S. Ye.; Грохольський, В. Л.; Кайда, Н. І.; Албул, С. В.; Рижков, Є. В.; Трехуб, С. Є. (My University, 2020)
Lifelong learning is one of the main trends in educational and social policy in Europe, aimed at ensuring professional realization and social integrity of an individual. The article describes cognitive and metacognitive aspects of the formation of learning competence, as well as predisposition of law students to lifelong learning. A survey of 218 students and masters was conducted, data on the most popular and effective forms of knowledge acquisition (experience of formal, nonformal and informal learning over the past year), plans for further education and career development were collected. The dynamics of learning at different years of study is described. A group of students with pronounced learning and focus on lifelong learning (45% of the sample) was identified. A comparative analysis of two samples was carried out and qualities that could be considered markers of the LLL orientation were identified: a high level of metacognitive knowledge and metacognitive activity, reflective competence (at the cognitive, metacognitive and personal level), internal involvement in learning, focus on achieving professionalism and personal development, general self-efficacy, the prevalence of progressive and creative motives over consumer ones. Conclusions are drawn about the predominant role of metacognitions and personality determinants in the formation of lifelong learning competency among students. Reflection aimed at recognizing one’s own cognitive processes and understanding their contribution to personal development is the main mechanism for the formation of meta-cognitive abilities. The results obtained in the study determine the ways of pedagogical support and psychological intervention to ensure the development of lifelong learning competencies in different categories of students.
Keywords: lifelong learning; educational competence; cognitive abilities; metacognitive competencies; reflection; individual’s self-development